2013
DOI: 10.1063/1.4773247
|View full text |Cite
|
Sign up to set email alerts
|

Thermal annealing effect on material characterizations of β-Ga2O3 epilayer grown by metal organic chemical vapor deposition

Abstract: In this work, a single-crystalline β-Ga2O3 epilayer was grown on (0001) sapphire at low temperature by low-pressure metal organic chemical vapor deposition. The optimized parameters for the chamber pressure, oxygen flow, and growth temperature were 15 Torr, 200 sccm, and 500 °C, respectively. The β-Ga2O3 epilayer was fabricated as a metal-semiconductor-metal solar-blind deep ultraviolet photodetector. Due to the gallium oxide grown at low temperature, the as-grown β-Ga2O3 epilayer was annealed at 800 °C in atm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 10 publications
2
49
0
Order By: Relevance
“…They were responsible in trapping the photogenerated electron or hole carriers. The smooth surface would lead to the low surface area and then the low surface density states for the annealed ZnGa 2 O 4 film, which is beneficial for the improved performance of the PD 14,15 .
Figure 2Atomic force microscope images of thin-film surfaces and surface roughness of as-grown and annealed ZnGa 2 O 4 thin films.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were responsible in trapping the photogenerated electron or hole carriers. The smooth surface would lead to the low surface area and then the low surface density states for the annealed ZnGa 2 O 4 film, which is beneficial for the improved performance of the PD 14,15 .
Figure 2Atomic force microscope images of thin-film surfaces and surface roughness of as-grown and annealed ZnGa 2 O 4 thin films.
…”
Section: Resultsmentioning
confidence: 99%
“…High Idark for as-grown ZnGa 2 O 4 films can be inter-related to the high intrinsic defects, such as oxygen vacancies and/or surface density state in the ZnGa 2 O 4 films. The low photocurrent implied that the defect concentration was reduced, which resulted in low conductivity 15 . Surface-related defects can act as adsorption sites or trapping center to capture free electrons in ZnGa 2 O 4 films.…”
Section: Resultsmentioning
confidence: 99%
“…On account of the intrinsic lower dark current and faster response speed, MSM photodetectors based on β‐Ga 2 O 3 have attracted grand interest and been extensively studied recently . Heretofore, various electrode materials including Ti/Au, Ni/Au, indium zinc oxide (IZO), and graphene have been utilized to form Schottky barrier contacts with β‐Ga 2 O 3 .…”
Section: Ga2o3mentioning
confidence: 99%
“…Huang et al annealed the epilayer at 800°C under different ambient to improve the crystallinity and found that the X-ray diffraction of β-Ga 2 O 3 annealed in a nitrogen environment for 15 min has the strongest peak while annealing in an oxygen environment for 30 min shows diminished performance due to the oxygen content reaching a saturation state during annealing. In air ambient annealing which used both oxygen and nitrogen, the observed crystalline properties were better than those obtained from purely oxygen annealing [13]. Up to now, no reports have systematically studied the annealing effect of (GaIn) 2 O 3 films.…”
Section: Introductionmentioning
confidence: 85%